TaNF-YB11, a gene of NF-Y transcription factor family in Triticumaestivum, confers drought tolerance on plants via modulating osmolyte accumulation and reactive oxygen species homeostasis - Ying-jia ZHAO; Yan-yang ZHANG; Xin-yang BAI; Rui-ze LIN; Gui-qing SHI; Ping-ping DU; Kai XIAO (Journal of Integrative Agriculture, 2022)
Transcription factors (TFs) regulate diverse stress defensive-associated physiological processes and plant stress responses. We characterized TaNF-YB11, a gene of the NF-YB TF family in Triticum aestivum, in mediating plant drought tolerance. TaNF-YB11 harbors the conserved domains specified by its NF-YB partners and targets the nucleus after the endoplasmic reticulum (ER) assortment. Yeast two-hybrid assay indicated the interactions of TaNF-YB11 with TaNF-YA2 and TaNF-YC3, two proteins encoded by genes in the NF-YA and NF-YC families, respectively. These results suggested that the heterotrimer established among them further regulated downstream genes at the transcriptional level. The transcripts of TaNF-YB11 were promoted in roots and leaves under a 27-h drought regime. Moreover, its upregulated expression levels under drought were gradually restored following a recovery treatment, suggesting its involvement in plant drought response. TaNF-YB11 conferred improved drought tolerance on plants; the lines overexpressing target gene displayed improved phenotype and biomass compared with wild type (WT) under drought treatments due to enhancement of stomata closing, osmolyte accumulation, and cellular reactive oxygen species (ROS) homeostasis. Knockdown expression of TaP5CS2, a P5CS family gene modulating proline biosynthesis that showed upregulated expression in drought-challenged TaNF-YB11 lines, alleviated proline accumulation of plants treated by drought. Likewise, TaSOD2 and TaCAT3, two genes encoding superoxide dismutase (SOD) and catalase (CAT) that were upregulated underlying TaNF-YB11 regulation, played critical roles in ROS homeostasis via regulating SOD and CAT activities. RNA-seq analysis revealed that numerous genes associated with processes of ‘cellular processes’, ‘environmental information processing’, ‘genetic information processing’, ‘metabolism’, and ‘organismal systems’ modified transcription under drought underlying control of TaNF-YB11. These results suggested that the TaNF-YB11-mediated drought response is possibly accomplished through the target gene in modifying gene transcription at the global level, which modulates complicated biological processes related to drought response. TaNF-YB11 is essential in plant drought adaptation and a valuable target for molecular breeding of drought-tolerant cultivars in T. aestivum.